Penanggulangan Bencana Pasca Angin Puting Beliung- Hujan Deras di Universitas Sumatera Utara (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
Natural disasters are a phenomenon that cannot be avoided. Indonesia is one of the countries vulnerable to natural disasters. Based on data from the Indonesian Central Bureau of Statistics (BPS), it was concluded that extreme weather changes were the second most cases in Indonesia with 1,261 cases and in North Sumatra with 44 cases, which resulted in tornadoes and heavy rain. In line with this, the phenomenon of tornadoes and heavy rain has occurred in one of the cities in North Sumatra province, namely in Medan City, especially in the campus area of the University of North Sumatra, which resulted in several damages in several faculties and several fallen trees in the area around the University of North Sumatra campus.